Chidamide Reverses Fluzoparib Resistance in Triple-Negative Breast Cancer Cells - Li, Xinyang; Yuan, Xiang; Wang, Ziming; Li, Jing; Liu, Zhiwei; Wang, Yukun; Wei, Limin; Li, Yuanpei; Wang, Xinshuai (Frontiers in Oncology, 2022)
Poly (ADP-ribose) polymerase inhibitor (PARPi) resistance is a new challenge for anti-tumor therapy. The purpose of this study was to investigate the reversal effects of chidamide on fluzoparib-resistance, a PARPi, and its mechanism of action. A fluzoparib-resistant triple-negative breast cancer (TNBC) cell line was constructed, and the effects of chidamide and fluzoparib on drug-resistant cells were studied in vitro and in vivo. The effects of these drugs on cell proliferation, migration, invasiveness, the cell cycle and apoptosis were detected using an MTT assay, wound healing and transwell invasion assays and flow cytometry. Bioinformatics was used to identify hub drug resistance genes and western blots were used to assess the expression of PARP, RAD51, MRE11, cleaved Caspase9 and P-CDK1. Xenograft models were established to analyze the effects of these drugs on nude mice. In vivo results showed that chidamide combined with fluzoparib significantly inhibited the proliferation, migration and invasiveness of drug-resistant cells, and restored fluzoparib sensitivity to drug-resistant cells. The combination of chidamide and fluzoparib significantly inhibited the expression of the hub drug resistance genes RAD51 and MRE11, arrested the cell cycle at the G2/M phase and induced cell apoptosis. The findings of this work show that chidamide combined with fluzoparib has good antineoplastic activity and reverses TNBC cell resistance to fluzoparil by reducing the expression levels of RAD51 and MRE11.